Predictive immunohistochemical indicators of regional metastasis of laryngeal squamous cell carcinoma. - Kovtunenko, A. V.; Shportko, B. V.; Shponka, I. S.; Poslavska О. V. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. The comprehension of molecular events that underlie malignant transformation of squamous cell epithelium could not only extend the knowledge about the etiology of this process, but also is basic for predictive markers and target therapy. Objective. The article analyzes the predictive immunohistochemical indicators of regional metastasis of laryngeal squamous cell carcinoma. Methods. In the study we used the original biopsy material from 70 patients with laryngeal squamous cell carcinoma T3-4N0-3M0 (69 men and 1 woman) aged from 33 to 74 during the period 2011-2014. The primary monoclonal antibodies for cyclin D1, CD34 and VEGF (TermoScientific, USA) were used. Results. There were significant correlation between increased expression of markers cyclin D1 (р<0,0001), VEGF (р=0,018), extension of microvessel density (р=0,032) and presence of regional metastasis of laryngeal squamous cell carcinoma. Conclusion. The significant increase of microvessel density and expression of VEGF and cyclin D1markers in the laryngeal squamous cell carcinomas proves their predictive importance.